Searching the Internet and Assessing Information Quality - Heiko Spallek (Association of American Medical Colleges, 2011)
Abstract Teaching search skills is often considered unnecessary for the current generation of incoming dental students. While it is true that the degree of computer literacy for incoming students is gradually rising, on the other hand even basic knowledge about computers is far from universal. For instance, a 2006 study found that nearly half of 308 participating college-age students enrolled in courses at the College of Health Sciences at Midwestern University had trouble discriminating between primary and secondary sources. In addition, two-thirds of them were unable to understand or apply Boolean operators when searching. This resource then attempts to improve students' information fluency or information literacy, which can be defined as the ability to access, evaluate, and use information from a variety of sources. As the Horizon 2010 report points out, "Digital media literacy continues its rise in importance as a key skill in every discipline and profession. The challenge is due to the fact that despite the widespread agreement on its importance, training in digital literacy skills and techniques is rare in any discipline."